THE EFFECTIVENESS OF ANXIETY ASSISTANCE TO TEENAGE GIRL IN FACING PUBERTY AT ORPHANAGE - Sholaikhah Sulistyoningtyas; Andri Nur Sholihah (Siklus : Journal Research Midwifery Politeknik Tegal, 2021)
Anxiety is when the individual feels worried/anxious; uncontrolled tension and discomfort about something terrible that was about to happen. Adolescence is marked by puberty, characterized by rapid physical changes, experiencing menarche, psychological changes, and the emergence of secondary sex characteristics, such as the growth of breasts, enlarged hips, and fine growth hairs in the armpit area, and the smell of sweat. Adolescent anxiety often occurs in young women when facing puberty. This study aimed to determine the effectiveness of the assessment of anxiety in facing puberty in adolescents. The research method used a quasi-experimental with a sampling technique using a total sampling of 52 adolescents. The analysis technique used Wilcoxon. The study results with a significance value of 0.000 show that mentoring is very effective in dealing with anxiety at puberty for young women.     Keyword: Adolescent Mentoring, Anxiety, Puberty